The Transfer of the New Biography: Virginia Woolf and Lytton Strachey in Interwar Poland - Paulina Pająk (Acta Universitatis Wratislaviensis. Anglica Wratislaviensia)
This article presents the cultural transfer of the new biography, which attracted avid interest in interwar Poland. It reconstructs how modernist publishing networks circulated Virginia Woolf’s biofiction and Lytton Strachey’s modernist biographies, using previously unexamined archival correspondence from the UK and Polish archives, along with interwar newspapers and magazines from digital and print repositories in Poland. The article focuses on strategies of cultural transfer as developed by the publishing house Rój that launched Strachey’s books, as well as on diverse cultural mediators who reviewed and popularized Woolf’s and Strachey’s works. The early reception of Woolf’s and Strachey’s biographical experiments is examined in the context of the growth of Central European modernism(s) and interwar changes at the global literary marketplace.